Experimental and theoretical studies on polar Diels–Alder reactions of 1-nitronaphathalene developed in ionic liquids - Mancini, Pedro M. E. (2013)
The reactions between 1-nitronaphthalene 1 and two nucleophilic dienes, Danishefsky´s diene 2 and 1-trimethylsilyloxy-1,3-butadiene 3, to yield phenanthrenols 7 and 8 developed in protic and aprotic ionic liquids (ILs) with an imidazolium cation base permit to conclude that the reactions occur in better experimental conditions than in molecular solvents. The yields obtained with protic ILs are better than those observed with aprotic ILs. In this sense, the higher yields obtained with aprotic ILs, (working at 60ºC, 48 h) are comparable with the lower yields observed in protic ILs (60 ºC, 24 h). DFT calculations for the reaction of 1-nitronaphthalene 1 with diene 3, in the absence and in the presence of tetrafluoroborate of 1-metilimidazolium [HMIM] [BF4] as protic ILs, indicate that this reaction is a domino process that comprises two consecutive processes: i) a polar Diels-Alder (P-DA) reaction between 1 and 3, and ii) an elimination of nitroso acid 5 to yield dihydrophenanthrene 11. Thermodynamic calculations indicate that while the first reaction is the rate-determining step of this domino process, the nitroso acid elimination is the driving force responsible for the formation of dihydrophenanthrene 11. Implicit and explicit solvent effects indicate that while the hydrogen bond formation between HMIM and one oxygen atom of the nitro groups favour the two reactions, implicit solvent effects modelled by PCM decelerate the P-DA reaction by a large solvation of reagents. Finally, DFT analysis of reagents offers an explanation of the catalytic role of protic ILs in these P-DA reactions.